2022
DOI: 10.3390/s22249688
|View full text |Cite
|
Sign up to set email alerts
|

Detection Methods for Multi-Modal Inertial Gas Sensors

Abstract: We investigate the rich potential of the multi-modal motions of electrostatically actuated asymmetric arch microbeams to design higher sensitivity and signal-to-noise ratio (SNR) inertial gas sensors. The sensors are made of fixed–fixed microbeams with an actuation electrode extending over one-half of the beam span in order to maximize the actuation of asymmetry. A nonlinear dynamic reduced-order model of the sensor is first developed and validated. It is then deployed to investigate the design of sensors that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Bistable mechanisms, composed of elastic beams or membranes, are widely employed across various MEMS applications, including microrobotics 36 , switch 37 , resonators 38 , sensors 39,40 , and actuator 41 , owing to their simplicity, low actuation energy, large stroke with small restoring forces, and snap-through behavior. Among these, beam-type bistable mechanisms are particularly prevalent in MEMS as compliant mechanisms, favored for their straightforward structure and negative stiffness properties.…”
Section: Modeling and Design Of The Anti-spring Mechanismmentioning
confidence: 99%
“…Bistable mechanisms, composed of elastic beams or membranes, are widely employed across various MEMS applications, including microrobotics 36 , switch 37 , resonators 38 , sensors 39,40 , and actuator 41 , owing to their simplicity, low actuation energy, large stroke with small restoring forces, and snap-through behavior. Among these, beam-type bistable mechanisms are particularly prevalent in MEMS as compliant mechanisms, favored for their straightforward structure and negative stiffness properties.…”
Section: Modeling and Design Of The Anti-spring Mechanismmentioning
confidence: 99%
“…Najar et al [24] found that the shifts in the natural frequency and bifurcation location of inertial sensors due to added masses are similar in size. We, therefore, postulate that the threefold difference we observed here is due to the absence of electrostatic fields in experiment # 5 and their presence in experiment # 6.…”
Section: Dynamic Detection Modementioning
confidence: 99%
“…This is attributed to their small size, lightweight, high accuracy, portability, affordability, and their real-time operational capability [1]. Consequently, they found widespread adoption in a multitude of applications, such as pressure sensors [2], temperature sensors [3], force sensors [4], accelerometers [5], gyroscopes [6], and gas sensors [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%